Activation of BK Channels Prevents Hepatic Stellate Cell Activation and Liver Fibrosis Through the Suppression of TGFβ1/SMAD3 and JAK/STAT3 Profibrotic Signaling Pathways - Yang, Linli; Han, Bo; Zhang, Man; Wang, Ya-Hui; Tao, Kun; Zhu, Michael X.; He, Kunyan; Zhang, Zhi-Gang; Hou, Shangwei (Frontiers in Pharmacology, 2020)
Large-conductance and Ca2+-activated K+ (BK) channels are expressed in human hepatic stellate cells (HSCs), where they have roles in normal hepatic microcirculation, as well as in portal hypertension in liver cirrhosis through the regulation of contractility in activated HSCs. Nevertheless, whether BK channel activity exerts protective effects against aberrant HSC activation and hepatic fibrosis is unknown. Here, we report that BK channels are expressed in activated primary rat HSCs as well as in a human HSC line. Moreover, whole-cell K+ currents recorded from activated HSCs were markedly increased by exposure to rottlerin, a BK channel-specific activator, but were inhibited by treatment with the BK channel-specific inhibitor, paxilline, suggesting that BK channels are functional in activated HSCs. Overexpression but not downregulation of the BK channel pore-forming alpha subunit, KCNMA1, led to reduced migration and collagen expression in activated HSCs. Consistently, rottlerin treatment suppressed the fibrogenic cell function both in vitro and in CCl4-induced liver fibrosis in vivo. Microarray and pathway analysis, combined with a luciferase reporter assay and western blotting, further showed that rottlerin treatment led to a significant downregulation of the profibrotic TGFβ1/SMAD3 and JAK/STAT3 signaling pathways, both in vitro and in vivo. Our findings not only link BK channel function to profibrotic signaling pathways, but also provide evidence that BK channel activation represents a promising therapeutic strategy for the treatment of liver fibrosis.